NATIONAL FOOD SECURITY TRANSFORMATION:INDONESIA'S AGRICULTURAL DIVERSIFICATION ANDINNOVATION STRATEGY TO REDUCE DEPENDENCE ONWHEAT IMPORTS AFTER THE UKRAINE CRISIS (2022-2024) - Raihanah Djamar; Della Evelin (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The Russia-Ukraine geopolitical crisis since 2022 has disrupted global supply chains, including the supply of wheat, which is a strategic food commodity of the world. Indonesia, as one of the largest wheat importing countries, has been significantly affected by price spikes and high import dependence. This study aims to analyze the transformation of national food security through agricultural diversification and innovation strategies in reducing dependence on wheat imports in the post-Ukraine crisis period (2022–2024). The approach used is qualitative with literature study methods and secondary data analysis from BPS, FAO, and the Ministry of Agriculture of the Republic of Indonesia. The results of the study show that food diversification based on local commodities such as sorghum, sweet potatoes, sago, and corn has increased policy support, both in the form of production incentives and research strengthening. Agricultural innovation through agroecotechnology approaches and strengthening local food ecosystems has also been proven to increase the productivity of wheat alternatives by 17.4% in 2023 compared to the previous year. However, challenges such as people's consumption preferences and limited food infrastructure remain major obstacles. This study recommends the integration of food diversification strategies with consumer education approaches and community-based technology investment to build national food independence in a sustainable manner.